(untitled) (Nordic Journal of Practical Theology, 2025)
This article explores the declining role of the Church of Sweden through an in-depth analysis of its contemporary Church language. Drawing on previously collected empirical material, the study shows how Christian language today often fails to connect with people’s everyday lives. The analysis identifies three core problems, each contributing to a gap between abstract expressions and lived experience. The findings challenge earlier research that primarily attributes the church’s decline to a lack of knowledge about Christian doctrine. Instead, the article suggests that secularization may partly stem from a distancing from a dysfunctional religious language, rather than from societal modernization alone.